ANALISIS IMPLEMENTASI GOOD GOVERNANCE DALAM PENGELOLAAN KEUANGAN DESA TIRTAYASA - Efi Tajuroh Afiah; Aris Trismayadi Nurizki; Nugrahini Kusumawati; Fatari Fatari (Yayasan Education and Social Center, 2026)
This study examined the implementation of good governance principles in the financial management of Tirtayasa Village, focusing on transparency, accountability, and community participation. The problem addressed in this research was the gap between normative governance regulations and their practical application at the village level, particularly in managing public financial resources. A descriptive qualitative approach with a case study method was employed. Data were collected through in-depth interviews, observation, and document analysis involving village officials, members of the Village Consultative Body, and community representatives. The findings showed that transparency had been implemented through formal information disclosure mechanisms, but public understanding of financial information remained limited. Accountability procedures were conducted in accordance with administrative requirements; however, they tended to emphasize compliance rather than performance and social accountability. Community participation occurred mainly during formal planning forums, yet involvement in monitoring and evaluation processes was minimal and dominated by local elites. The study concluded that the implementation of good governance in Tirtayasa Village had progressed at a procedural level but had not fully achieved substantive governance outcomes. Strengthening institutional capacity, improving financial literacy, and enhancing participatory accountability mechanisms were identified as essential steps to improve village financial governance and support sustainable local development.